An Unusual Case of Osteofibrous Dysplasia of Tibia in a Female Child: Osteofibrous Dysplasia of Tibia (GAIMS Journal of Medical Sciences, 2024)
Osteofibrous dysplasia (OFD) is an uncommon bone tumor characterized by a non-cancerous, developmental skeletal disorder. It comprises a fibrous matrix with immature bone tissue surrounded by osteoblasts, typically located in the cortex of long bones. Distinguishing between osteofibrous dysplasia, fibrous dysplasia, classical adamantinoma, and osteofibrous dysplasia-like adamantinoma can pose a diagnostic challenge. OFD is challenging to diagnose on histopathology alone without radiological and clinical correlation and we highlight the importance of the same. Therefore, initial clinico-radiological correlation must be followed by histopathological examination in guiding prompt inception of timely treatment. Here, we present a unique, uncommon case of OFD in a seven-year-old girl, wherein pathological fractures occurred due to an underlying bone lesion incidentally detected on X-ray.